Motivation of music students: School of Arts flute orchestra - Terrazas-Bañales, Francia (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Motivation plays a key role in promoting the development of skills and abilities of students. Intrinsic motivation is generated as a result of the genuine interest of the individuals; extrinsic motivation is generated by external factors as a benefit or reward. In any case, teachers have the capacity to influence their students’ motivation. In October 2016 the Autonomous University of Chihuahua School of Arts Flute Orchestra was formed as part of the project called School of Arts Flute Orchestra: Inclusion and group work between students and teachers. Research project, aimed at impacting on the performance of flute students. By means of qualitative research, the present article shares the results of the first interviews with the nine members of the group regarding motivation. The results show that intrinsic motivation is predominant in the first instance and that students present skills development, problem solving, a decrease of stage fright, and progress in their academic learning arising therefrom.